Application of communication strategies in the diffusion of agricultural innovations and technologies: the case of Amhara Regional Agricultural Research Institute, Ethiopia - Bewket Sisay Melaku; Enkuye Yizengaw Sefereh; Minas Hiruy Emunu; Dessalegn Yeshambel Wassie (Cogent Social Sciences)
Research institutions generate plenty of agricultural technologies which is capable of improving agricultural productivity. However, most of research outputs developed by research institutions were not properly communicated to the intended users. The current study, therefore, examined the factors that affect the application of communication strategies in the diffusion of agricultural innovations and technologies at the Amhara Regional Agricultural Research Institute (ARARI). To conduct this study, in-depth interviews and focus group discussions were conducted with senior experts from ARARI and purposefully selected farmers, respectively. The study also incorporated document analysis as a data collection instrument. The study predominantly used a qualitative approach to the research design. The findings of the study indicated that ARARI has dominantly followed traditional extension services that are slow, linear, hierarchical, and poorly funded. In relation to communication strategies, agricultural extension workers mostly used interpersonal communication strategies, while agricultural innovations and technologies were diffused to the end users. The findings also revealed that farmers still have a negative perception of the adoption and utilization of agricultural innovations and technologies that emerge from illiteracy, knowledge gaps, inexperience, fears, and lack of clear communication between extension workers and end users. Therefore, to clearly diffuse agricultural innovations and technologies to wider users, ARARAI as an institution should work largely in the adoption (cognitive activity), especially in awareness creation, knowledge management, and behavioral change communication to allow the users of the innovation as well as better to adopt and spread the technology to many users.